PELAKSANAAN PEMBELAJARAN MANDIRI PROGRAM PAKET C DI PKBM DAHLIA KECAMATAN SUKAJADI KOTA PEKANBARU - Viorent Oktalinata Sianturi Sianturi; Jaspar Jas; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to find out how the implementation of independent learning at the Dahlia Community Learning Activity Center (PKBM). The formulation of the problem in this research is how the implementation of independent learning in PKBM Dahlia, whether it has been implemented well. This research is a type of Naturalistic Descriptive research with a qualitative approach. This study consists of one variable, namely independent learning consisting of 5 indicators, namely (1) the Pyramid Objectives, (2) Learning Resources and Media, (3) Learning Place and Time, (4) Learning Methods, (5) Evaluation and Assessment . The subjects in the study were 3 people consisting of 1 core informant, 1 control informant and 1 observer informant. Data collection techniques are carried out with field observations, interviews and documentation. Based on the results of interviews with informants, it can be concluded that the implementation of self-learning program C package in PKBM Dahlia, Sukajadi District, Pekanbaru City on 2 destination indicators that the pyramid and sources and learning media have reached and can be categorized as feasible to use. And for the other 3 indicators namely place and time of learning, ways of learning, evaluation and assessment are categorized as not in accordance with the theory and procedures that should be and the implementation of activities is not on target.Key Words: Implementation, Independent Learning